Investigation of the structural, optical, elastic and electrical properties of spinel LiZn2Fe3O8 nanoparticles annealed at two distinct temperatures. Issue 70 (11th December 2019) - Bouokkeze, D.; Massoudi, J.; Hzez, W.; Smari, M.; Bougoffa, A.; Khirouni, K.; Dhahri, E.; Bessais, L.
Abstract : Nanoparticles of Li0.5 ZnFe1.5 O4 (LiZn2 Fe3 O8 ) with the spinel structure were prepared by a sol–gel auto-combustion method at two different annealing temperatures. Abstract : Nanoparticles of Li0.5 ZnFe1.5 O4 (LiZn2 Fe3 O8 ) with the spinel structure were prepared by a sol–gel auto-combustion method at two different annealing temperatures. X-ray diffractograms and Rietveld refinement confirmed the formation of the spinel structure. The morphology was analyzed by electron microscopy, which showed that the grains were composed of different crystallites. Elastic properties were determined from infrared spectroscopy. It was found that the elastic parameters increased with the increase in annealing temperatures. The band gap depends on the annealing temperature and it decreased on increasing the particle size. The conductivity of the specimen annealed at 500 °C followed either the Jonscher's model or Drude's model depending on the temperature range. This conductivity decreased when the annealing temperature was raised by 600 °C. AC conductivity was found to be controlled by the hopping model. A single relaxation phenomenon was evidenced for each sample from impedance analysis. The Nyquist diagram proved that the samples were simultaneously capacitive and resistive and also supported the presence of multiple relaxation times.